Haplotype analysis finds linkage disequilibrium in the IL‐12 gene in patients with HCV. Issue 7 (23rd April 2015) - Houldsworth, Annwyne; Metzner, Magdalena; Hodgkinson, Andrea; Shaw, Steve; Kaminski, Edward; Demaine, Andy G; Cramp, Matthew E
<x xml:space="preserve">Abstract</x> HCV is a major cause of liver disease worldwide. IL‐12 plays an essential role in the balance of T helper 1 (Th1) differentiation versus a T helper 2 (Th2) driven response from its naïve precursor. Linkage disequilibrium measures the degree to which alleles at two loci are associated and the non‐random associations between alleles at two loci. Haplotypes of the three IL‐12B loci studied were determined in the patient cases and the normal healthy control subjects. The frequency of the 12 possible IL‐12B haplotypes on the 3 loci was determined in subjects heterozygous at only one of the loci within the studied haplotype. Haplotype frequencies were compared between the patient groups and controls (n = 49) to determine if any preferential combination of markers occurred using chi‐squared and applying the Bonferroni correction. 45 HCV RNA negative patients; 88 HCV RNA positive patients; and 15 uninfected cases at high risk of HCV infection (EU) were studied. The haplotype "C" SNP of the 3′UTR with the "E" 4 bp deletion of the intron 4 region was in linkage disequilibrium (χ2 = 45.15, P < 0.001, 95% CL). The haplotype analysis of the insertion allele of the promoter with the deletion allele of the intron 4("E") IL‐12B polymorphism showed linkage disequilibrium (χ2 = 5.64, P = 0.02). Linkage disequilibrium of polymorphisms is reported in the IL‐12 gene in patients with HCV infection and contributes to the understanding of patient genotype and expected production of IL‐12, responding to infection. J. Med. Virol. 87:1207–1217, 2015. © 2015 Wiley Periodicals, Inc.